Rapid detection of lithium concentrations in oral fluid: short communication - Granger, Douglas A.; Parkin, Georgia M.; Buspavanich, Pichit; Findeisen, Peter; Rietschel, Marcella; McCarthy, Michael J.; Thomas, Elizabeth A. (Therapeutic drug monitoring, 2023)
Background: Lithium medication is considered to be the first-line treatment for bipolar disorder as a monotherapy, and for treatment-resistant depression with lithium augmentation. However, because of potential toxicity, lithium levels must be monitored frequently. Recent studies have demonstrated a significant correlation between lithium levels measured in serum and those detected in oral fluid, suggesting that oral fluid analysis may represent an easy, noninvasive means to monitor lithium levels. The aim of this study was to evaluate the analytical performance of rapid assays for lithium measurements in oral fluid. Methods: Levels of lithium in oral fluid from psychiatric patients (n = 108 in total) taking lithium medications were quantified using 2 rapid techniques: an automated clinical chemistry analyzer and a novel, commercially available colorimetric lithium assay. These results were compared with those obtained using inductively coupled plasma optical emission spectrometry (ICP-OES). Results: The mean and median oral fluid lithium levels in this cohort were 1.43-1.61 mM and 1.32-1.52 mM, respectively, depending on the method, with the overall range, across all methods, being 0.213-4.42 mM. Linear regression analysis showed excellent agreement between the oral fluid values measured using ICP-OES and the colorimetric method (r2 value = 0.926; P < 0.0001; slope = 1.084 ± 0.038). Similarly, excellent agreement was observed between ICP-OES and the automated method (r2 = 0.872; P < 0.0001; slope = 1.019 ± 0.057). Conclusions: These results demonstrate that lithium levels in oral fluid can be rapidly and reliably quantified using colorimetric approaches. These findings may facilitate the development of point-of-care lithium monitoring systems for use in oral fluid.
Gesehen am 07.10.2024